O isolamento social afetou o número de registros de duas espécies de Tyrannidae (Aves; Passeriformes) no estado de São Paulo - Peixoto, Beatriz Pereira (Universidade Federal de São Carlos, 2023)
On the 11th of March of 2020, the World Health Organization (WHO) declared that the outbreak of the coronavirus was characterized as a pandemic, which led to an abrupt change of the urban dynamic environment, that is called the “anthropause” by some authors. Thus, with less presence of humans in the urban centers, it was possible to observe some changes in bird behavior. This paper aimed to check if social distancing would have a significant impact on the records of 2 bird species in cities of the state of São Paulo. The project was executed during the pandemic, therefore, because of the circulation restrictions, it was conducted remotely, through online databases. The paper also expects to contribute to the study of the great impact that the unprecedented social distancing and change on the urban environments had on birds. Our hypothesis was that there would be a significant raise in the number of records of birds, in the period of the lockdowns, based on the less interference of humans in urban centers. Confirming our hypothesis, there was a significant difference in the number of records; however contradicting our predictions, the number of records was lower due to the social distancing. Overall, this result was attributed to some factors, including the limitations that the social distancing brought to the observers.
Social isolation affected the number of records of two species of Tyrannidae (Aves; Passeriformes) in the state of São Paulo, Brazil
Keywords: Ecologia urbana; Covid-19; Observação de aves; Ciência Cidadã; Tyrannus melancholicus; Myiodynastes maculatus; Urban ecology; Sars-Covid 19; Bird watching; Citzen science; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA TEORICA